Preliminary study on chemical mechanism of decrease of tetrodotoxin content in ovaries of a puffer fish Lagocephalus inermis (Temminck & Schlegel, 1850) fermented with rice bran - Hy, Le Ho Khanh; Ky, Pham Xuan; Ha, Dao Viet; Hong, Nguyen Thu; Vy, Phan Bao; Thiet, Doan Thi; Anh, Nguyen Phuong (Vietnam Journal of Marine Science and Technology, 2019)
Tetrodotoxins in salted and fermented ovaries with rice bran of a puffer fish Lagocephalus inermis (Temminck & Schlegel, 1850) during five months were determined by high-performance liquid chromatography with fluorometric detector (HPLC- FLD). The analysed results showed that the original ovaries contained only tetrodotoxin with content of 7.59 µg/g fresh weight. 4,9-Anhydrotetrodotoxin - an isomer which is less toxic than tetrodotoxin has been found in all ovary samples since the second month. Tetrodotoxin in the ovaries disappeared in the 4th month of the experiment. In addition, 4,9-anhydrotetrodotoxin level in ovaries increased during fermentation. The present study contributes to clarifying the chemical mechanism of decreasing tetrodotoxin content in fermented ovary of puffer fish.